Mathematical problem-solving ability with blended learning model of flipped classroom type assisted by learning video - Yanti, Nova Devi; Susanto, Andi; Utami, Nita Putri (IAIN Palangka Raya, 2024)
This research aims to analyze the differences in students' mathematical problem-solving abilities using the Flipped Classroom Type Blended Learning model assisted by learning videos compared to scientific Learning. The study employed a quasi-experimental method with a Randomized Control group-only design. The research population comprised all 286 eighth-grade students at SMP Negeri 5 Padang. Samples were selected using a random sampling technique, with class VIII.5 as the experimental class and class VIII.4 as the control class. The research instrument was a mathematical problem-solving ability test. Data analysis used a t-test. The results showed that students' mathematical problem-solving abilities taught using the Flipped Classroom Type Blended Learning model assisted by learning videos were higher than those using scientific Learning. This is evidenced by the experimental class average score of 72.54 is higher than the control class at 67.85 and t count (2.95) > t table (1.67).